2016
DOI: 10.5380/ce.v21i2.44241
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Associados À Representatividade Da Zona De Transformação Em Exames Citopatológicos Do Colo Uterino

Abstract: Objetivou-se analisar os fatores associados à representatividade da Zona de Transformação em exames citopatológicos para controle do câncer do colo do útero.Trata-se de um estudo retrospectivo de caráter quantitativo realizado por meio das análises dos exames citopatológicos registrados no Sistema de Informação do Câncer em 2014. A amostra final resultou em 1.157 laudos. Para a análise dos dados foi utilizado o software Statistical Package for the Social Sciences. Do total de exames, 96,88% foram realizados pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
0
12
0
7
Order By: Relevance
“…25 In addition, in some cases where the representativeness of the sample contributed to the non-identification of cervical neoplasia, it was observed that the cytopathological reports were represented only by ectocervix material, which were released with HSIL and LSIL (Low Grade Squamous Intraepithelial Lesion) results, but the histopathology revealed that it was actually adenocarcinoma. According to Gasparin et al, 26 the squamocolumnar junction (SCJ) and/or transformation zone are regions where more than 90% of the intraepithelial lesions are located, demonstrating the need for constant monitoring and qualification of the professionals involved in the collection of cytopathological material, so that the involvement of the cervical smears is avoided. 26 Factors such as subjectivity, training, experience, cytopathologist scrutiny ability, work overload, SCJ cells representativeness, adequate fixation, diagnostic difficulties (few scaly abnormal cells, small or inaccessible lesions, necrosis, bleeding, origin of lesions, diagnoses borderline), in addition to internal and external laboratory quality control, are essential for the screening of cervical cancer and, if not taken into account, may induce errors in the interpretation of cytomorphological criteria, making it impossible to carry out complementary tests and clinical followup of cervical cancer in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In addition, in some cases where the representativeness of the sample contributed to the non-identification of cervical neoplasia, it was observed that the cytopathological reports were represented only by ectocervix material, which were released with HSIL and LSIL (Low Grade Squamous Intraepithelial Lesion) results, but the histopathology revealed that it was actually adenocarcinoma. According to Gasparin et al, 26 the squamocolumnar junction (SCJ) and/or transformation zone are regions where more than 90% of the intraepithelial lesions are located, demonstrating the need for constant monitoring and qualification of the professionals involved in the collection of cytopathological material, so that the involvement of the cervical smears is avoided. 26 Factors such as subjectivity, training, experience, cytopathologist scrutiny ability, work overload, SCJ cells representativeness, adequate fixation, diagnostic difficulties (few scaly abnormal cells, small or inaccessible lesions, necrosis, bleeding, origin of lesions, diagnoses borderline), in addition to internal and external laboratory quality control, are essential for the screening of cervical cancer and, if not taken into account, may induce errors in the interpretation of cytomorphological criteria, making it impossible to carry out complementary tests and clinical followup of cervical cancer in women.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gasparin et al, 26 the squamocolumnar junction (SCJ) and/or transformation zone are regions where more than 90% of the intraepithelial lesions are located, demonstrating the need for constant monitoring and qualification of the professionals involved in the collection of cytopathological material, so that the involvement of the cervical smears is avoided. 26 Factors such as subjectivity, training, experience, cytopathologist scrutiny ability, work overload, SCJ cells representativeness, adequate fixation, diagnostic difficulties (few scaly abnormal cells, small or inaccessible lesions, necrosis, bleeding, origin of lesions, diagnoses borderline), in addition to internal and external laboratory quality control, are essential for the screening of cervical cancer and, if not taken into account, may induce errors in the interpretation of cytomorphological criteria, making it impossible to carry out complementary tests and clinical followup of cervical cancer in women. 27 Regarding the microorganisms morphologically identified by cytopathology, this study verified the predominance of cocci and/or bacilli (66.67%), followed by Gardnerella vaginalis (8.33%).…”
Section: Discussionmentioning
confidence: 99%
“…Isso deve-se ao fato do rastreio organizado, no qual a mulher que atinge a citada faixa etária é incluída no grupo prioritário e acompanhada durante todo o período preconizado 16 , proporcionando a detecção e o tratamento das inflamações ainda nas fases iniciais. Estudos demonstram a busca pela realização do exame, para além da faixa etária preconizada 16,17 , o que, segundo dados do MS, não tem impacto na redução da incidência ou mortalidade por câncer do colo do útero 4 , mas pode detectar inflamações cérvico-vaginais, propiciando o tratamento resolutivo ainda na APS, conforme recomendado por esse nível de atenção.…”
Section: Resultsunclassified
“…Pode desenvolver-se a partir da exposição do epitélio glandular endocervical ao Ph da vagina, ocorrendo estímulo e proliferação das células glandulares de reserva (LIMA et al, 2012). De forma que um novo epitélio substitui progressivamente o epitélio glandular endocervical, constituindo-se assim a Zona de Transformação (ZT), a qual é considerada crítica na origem do carcinoma de colo uterino e onde localizam-se mais de 90% das lesões que antecedem o câncer de colo de útero (GASPARIN et al, 2016). A ZT é localizada no limite entre o epitélio escamoso da ectocérvice e o epitélio colunar da endocérvice (FERNANDES et al, 2013).…”
Section: Colo Do úTerounclassified
“…Chen et al (2014), descrevem que a gravidez mantém a zona de transformação (ZT) da cérvice durante muitos anos, facilitando a exposição ao HPV e outros fatores de risco, além disso sabe-se que a ZT é uma zona crítica na origem do câncer cervical (GARCIA et al, 2014;GASPARIN et al, 2016), mudanças hormonais induzidas pela gravidez como o aumento no nível de estrógeno e progesterona, podem modular a resposta imune do HPV juntamente com a persistência do vírus (CHEN et al, 2014). Outro questionamento a ser levado em consideração é se as mulheres que fazem uso de ACO poderiam ter uma menor prevalência ao uso da camisinha e uma maior liberdade sexual com um maior número de parceiros sexuais, influenciando diretamente no aumento da chance de contrair a infecção pelo HPV.…”
Section: Correlação Das Características Comportamentais Clínicas E Bunclassified